Synthetic and spectroscopic studies of indolizine derivatives - Bode, Moira Leanne (Rhodes University, Faculty of Science, Department of Chemistry, 1994)
The crystalline compound resulting from thermal cyclization of the Baylis-Hillman product, methyl 3-hydroxy-2-methylene-3-(2-pyridyl)propanoate, has been identified as the indolizine derivative, methyl indolizine-2-carboxylate, and this approach involving the reaction of pyridine-2-carboxaldehydes and acrylate analogues has been established as a general route to 2-substituted indolizines. The ease of cyclization the Baylis-Hillman products to indolizines has been shown to increase by converting the hydroxy group to an acetoxy group, and a range of acetylated Baylis-Hillman products were prepared and cyc1ized to the corresponding 2-substituted indolizines, generally in good overall yield. In the reaction of pyridine-2-carboxaldehyde and methyl vinyl ketone, the intermediate cyclized readily and directly to the corresponding indolizine. One- and two-dimensional ¹H and ¹³C NMR analysis of the 2-substituted indolizine products has permitted complete assignment of all ¹H and ¹³C NMR signals, as well as the measurement of all coupling constants for these compounds. A kinetic and mechanistic study has been conducted on the Baylis-Hillman reaction using ¹H NMR spectroscopy. A range of substrates has been examined and the reaction has been found to be third-order overall. A mechanism involving an addition - elimination sequence is proposed, which fits the kinetic data and accounts for observed substituent effects. Reaction of N,N-dimethylacrylamide with pyridine-2-carboxaldehyde in the presence of the tertiary amine catalyst, DABCO, in chloroform, yielded an unexpected product which has been identified by single crystal X-ray diffraction analysis as 1-(2,2,2-trichloro-1-hydroxyethyl)pyridine. Attempted extension of the general indolizine route to the preparation of chromene systems by reacting salicylaldehyde with methyl acrylate in the presence of DABCO, also led to an unexpected, crystalline material, identified by single crystal X-ray diffraction analysis as the coumarin derivative, 3-[(2-formylphenoxy)methyl]coumarin.A series of chloroquine analogues have been prepared from indolizine-2-carboxylic acid, pyrrolo[I,2-a]quinoline-2-carboxylic acid and imidazo[I,2-a]pyridine-2-carboxylic acid by reaction with suitable amines in the presence of the coupling reagent 1, I' -carbonyldiimidazole. This route has been shown to be a vast improvement on earlier procedures and has provided access to both secondary and tertiary indolizine-2-carboxamides. A range of N,N-dialkylindolizine-2-carboxamides have been prepared by this route, and the influence of substituents on their N-CO rotational energy barriers has been determined using variable temperature ¹H and ¹³C NMR techniques. Intercalation with natural DNA by both chloroquine and the synthesized chloroquine analogues has been examined using UV spectrophotometry, and ¹H and ³¹P NMR spectroscopy. The pyrrolo[I,2-a]quinolines have been shown to be DNA intercalators with binding affinities similar to that of the known antimalarial intercalator, chloroquine. In a preliminary study the synthesis of a short oligonucleotide has been undertaken and changes have been observed in the ¹H and ³¹P NMR spectra of the oligonucleotide on addition of the intercalator, chloroquine.
Keywords: Indole alkaloids -- Derivatives; Spectrum analysis; Chemistry, Organic; DNA -- Synthesis